Land Registration: Improving Digital Integrated System - Liong; Saleng, Abrar ,; Patittingi, Farida; Lahae, Kahar (International Journal of Psychosocial Rehabilitation, 2020)
The implementation of land registration has been done digitally integrated, whether the rules on land registration is still relevant in the land registration integrated digital as well as to provide legal certainty of land rights in Indonesia. This article is an empirical legal research with qualitative approach. The results show that the implementation of an integrated digital land registry has not been implemented as they should due to the regulations issues. The ideal concept in integrated digital land registration is to prepare a National Land Base data centers that store data and prepare land legal instruments governing land registration are done digitally integrated so as to provide legal certainty of land rights.